Turning hydrophilic bacteria into biorenewable hydrophobic material with potential antimicrobial activity via interaction with chitosan. (April 2017) - Hanpanich, Orakan; Wongkongkatep, Pravit; Pongtharangkul, Thunyarat; Wongkongkatep, Jirarut
Graphical abstract: Highlights: Antimicrobial interface material derived from L. lactis IO-1 and chitosan. Smaller sizes of bacteria produce more stable network with chitosan. Autolysis and chitosanase active bacteria are not suitable for network formation. Abstract: Alteration of a bacteriocin-producing hydrophilic bacterium, Lactococcus lactis IO-1, into a hydrophobic material with potential antimicrobial activity using chitosan was investigated and compared with five other bacterial species with industrial importance. The negatively charged bacterial cells were neutralized by positively charged chitosan, resulting in a significant increase in the hydrophobicity of the bacterial cell surface. The largest Gram-positive B. megaterium ATCC 14581 showed a moderate response to chitosan while the smaller E. coli DH5α, L. lactis IO-1 and P. putida F1 exhibited a significant response to an increase in chitosan concentration. Because L. lactis IO-1 is a good source for natural peptide lantibiotic that is highly effective against several strains of food spoilage organisms and pathogens, hydrophobic material derived from L. lactis IO-1 and chitosan is a promising novel material with antimicrobial activity for the food and pharmaceutical industries.